Non Finance Versus Finance Factors' Influence on Banks' Profitability : Evidence from Malaysia - Rosmariniwati, Ismail (2012)
The purpose of this study is to investigates the factors that influence the profitability determinants on banks in Malaysia. This study covers six (6) anchor banks in Malaysia i.e. CIMB Bank Berhad, Maybank Berhad, Public Bank Berhad, Hong Leong Bank Berhad, RHB Bank Berhad and Affin Bank Berhad during the period of 2006-2010. The objective of this study are firstly to find out the non finance factor and finance factor influence the banks’ profitability in Malaysia. Second objective is to identify the non finance versus finance factors influence on the profitability and third objective is to differentiate the significant profitability of finance and non finance factors. The study used ROE as a dependent variable to estimate the bank’s profit. The independent variables used in the study consisted of 11 variables namely capital adequacy ratio (CAR), capital to asset ratio (CR), leverage (LEV), bank size (SIZE), loan deposits (LD), loan loss provision (LLP), capital investment intensity (CII), liquidity assets (LIQ), Base Lending Rate (BLR), inflation rate (IFL), and gross domestic product (GDP). Multiple regression analysis has applied to examine the significance contribution of these variables in the bank’s profitability. The results however show that only SIZE and LIQ are significant at the 10% confidence level.